Diskriminasi Gender dalam Rumah Tangga - Rika Jatnika (Syntax Idea)
Domestic violence is actually nothing new. However, all this time it has always been kept secret or covered up by the family, as well as by the victim himself or his family. Online mass media, as a channel for people's aspirations and containing news about current phenomena, does not lag behind in presenting this news. The focus of this research is looking at the media's perspective in reporting on this problem using descriptive research methods through the Sara Mills critical discourse analysis model approach, which is published in online media. This research discusses the role of women in news about domestic violence. The aim of this research is to reveal the author's purpose in writing text based on the subject-object position and the reader. This research uses a qualitative descriptive method with the Sara Mills model theory which makes feminist discourse the center of the study. The data in this research are expressions related to the discourse analysis model of Sara Mills. The data source used in this research is news with the title Chronology of Domestic Violence against Venna Melinda, Often Experiencing Violence but Covering It Up on the mass media Kompas.com. Data analysis techniques are carried out by data reduction, data presentation and drawing conclusions. The level of violence against women as objects is still high. This happens due to several factors, including culture and the behavior of the subjects of violence. This shows the existence of internal and external factors. news selected in Critical Discourse Analysis that shows the suffering of women. Sara Mills' analysis is the theory used in this critical discourse analysis which is an expression of the presence of women in the news. Women are victims of domestic violence.